METODE MENINGKATKAN MINAT BELAJAR IPA: SEBUAH STUDI META-SINTESIS - Afendi, Arief Hidayat; Qisthi, Chairul Umam; Abidin, Zaenal (Jurnal PGSD, 2023)
Abstract Students will focus on one thing that grabs their attention and that can be said as an interest in students. The purpose of this research is to identify any methods that can increase students' interest in learning science. The research method uses a meta-synthetic method which is a method of summarizing research results, with a meta-ethnographic approach that aims to develop new theories to complement existing theories. The search was carried out through a database of electronic journals, including ERIC, Science Direct, SAGE journals, and Google Scholar with a range of publications in the last 5 years. The results obtained indicate that the method of increasing interest in science learning includes the use of learning media, learning models, learning methods and other methods that can increase interest in the learning process and show results that show it can increase interest in learning science for students. These methods of increasing interest in learning are not only applied to science learning, but can be applied to other learning that requires increasing interest in learning in students and according to the character of the learning. Keywords: Interest in learning science, learning media, learning models, learning methods. Abstrak Peserta didik akan terfokus pada satu hal yang menyita perhatiannya dan itu dapat dikatakan sebagai sebuah minat dalam diri peserta didik. Tujuan penelitian ini adalah untuk mengidentifikasi metode apa saja yang dapat meningkatkan minat belajar IPA bagi peserta didik. Metode penelitian menggunakan metode meta-sintesis yang merupakan metode merangkum hasil-hasil penelitian, dengan pendekatan meta-etnografi yang bertujuan untuk mengembangkan teori baru untuk melengkapi teori yang sudah ada. Penelusuran dilakukan melalui database jurnal elektronik diantaranya, ERIC, Science Direct, SAGE journals, dan Google Scholar dengan rentang publikasi 5 tahun terakhir. Hasil penelitian yang didapat menunjukan bahwa metode meningkatkan minat belajar IPA diantaranya penggunaan media pembelajaran, model pembelajaran, metode belajar dan metode lain yang dapat meningkatkan minat pada proses pembelajaran dan menunjukan hasil yang menunjukan dapat meningkatkan minat belajar IPA bagi peserta didik. Metode-metode meningkatkan minat belajar tersebut tidak hanya untuk diterapkan pada pembelajaran IPA, melainkan dapat diterapkan untuk pembelajaran lain yang memerlukan peningkatan minat belajar pada peserta didik dan sesuai dengan karakter pembelajarannya Kata Kunci : Minat Belajar IPA, Media Pembelajaran, Model Pembelajaran, Metode Belajar.